A Tau Class Glutathione-S-Transferase is Involved in Trans-Resveratrol Transport Out of Grapevine Cells - Martínez-Márquez, Ascensión; Martínez-Esteso, María J.; Vilella-Antón, María T.; Sellés-Marchart, Susana; Morante-Carriel, Jaime A.; Hurtado, Elias; Palazon, Javier; Bru-Martínez, Roque (Frontiers in Plant Science, 2017)
Vitis vinifera cell cultures respond to pathogens and elicitors by synthesising and extracellularly accumulating stilbenoid phytoalexins. Large amounts of trans-resveratrol (t-R) are produced when a cell culture is elicited with methylated cyclodextrins (MBCD), either alone or combined with methyl jasmonate (MeJA). t-R transport to the extracellular medium, which represents the apoplastic space, would place this antifungal defence right in the battlefield to efficiently fight against pathogen attack. Yet despite their physiological relevance, these transport pathways are mostly unknown. A broad hypothesis-free DIGE-based proteomic experiment of a temporal series of elicited grapevine cell cultures was performed to explore the expression profiles of t-R biosynthetic proteins and other co-expressing proteins potentially involved in such a cell response. A correlation between two tau class glutathione-S-transferases (GSTs) with several stilbene synthase and phenylalanine ammonia-lyase isoforms, and with the t-R metabolite itself, was found and further assessed by a qRT-PCR gene expression analysis. The best candidate, GSTU-2, was cloned from the cDNA of the MBCD+MeJA-elicited grapevine cells and used for Agrobacterium-mediated grapevine cell transformation. The non-elicited lines that overexpressed GSTU-2 displayed an extracellular t-R accumulating phenotype, but stabilisation of t-R required the addition to culture medium of adsorbent compounds, e.g., PVP or β-cyclodextrin. The wild-type cell cultures accumulated no t-R, not even in the presence of adsorbents. The transient expression of the GSTU-2-GFP fusion proteins in grapevine cells showed localisation in the plasma membrane, and the immunoprecipitation of HA-tagged GSTU-2 revealed its interaction with HIR, a plasma membrane-bound protein. These findings are consistent with a functional role in transport. This is the first report providing several pieces of experimental evidence for the involvement of a specific tau class GST in t-R transport to the extracellular medium.